2017
DOI: 10.5114/pjp.2017.67614
|View full text |Cite
|
Sign up to set email alerts
|

Association of infiltrating cells with microvessel density in oral squamous cell carcinoma

Abstract: Several lines of evidence indicate that immune cells in the tumor microenvironment play an important role in regulating tumor progression. An immunohistochemical method was used to examine the abundance of natural killer (NK) cells, mucosal dendritic cells (DCs), macrophages, mast cells, and microvessel density in 78 cases of oral squamous cell carcinoma (OSCC): with better prognosis -OSCCBP (n = 37), and with poorer prognosis -OSCCPP (n = 41), and 18 controls. The mean numbers of macrophages and microvessels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Of the 46 articles that were eligible for inclusion, 13 assessed classical NK cell markers. [26][27][28][29][30][31][32][33][34][35][36][37][38] The activating markers group existed of three articles, [39][40][41] the inhibiting markers group of 5 [42][43][44][45][46] and the death receptor group of 25. Figure 1 provides an overview of study selection.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 46 articles that were eligible for inclusion, 13 assessed classical NK cell markers. [26][27][28][29][30][31][32][33][34][35][36][37][38] The activating markers group existed of three articles, [39][40][41] the inhibiting markers group of 5 [42][43][44][45][46] and the death receptor group of 25. Figure 1 provides an overview of study selection.…”
Section: Study Selectionmentioning
confidence: 99%
“…The four articles that mentioned hazard ratios [26][27][28][29] were selected for meta-analysis after critical appraisal; the forest plot is shown in figure 2. [26][27][28][29][30] The pooled meta-analysis showed an advantage for high CD56+/CD57+ NK cells regarding OS (pooled HR 0.19 CI 0.11-0.35) ( Figure 2). Some studies mentioned no correlation between CD56+ NK cell number and OS or recurrence-free survival (RFS) or between CD57+ NK cells and OS (de Carvalho Fraga et al: OR 1.04,CI 0.44-2.46, p 0.93) or DFS.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…Other studies have shown divergent results. StaSikOwSka-Kanicka et al 12 also associated the density of infiltrative cells and microvessels in OSCC and observed a significantly lower number of mast cells in lesions with unfavorable prognoses when compared to those with favorable prognoses and proposed that the deficiency of these cells in malignant lesions is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Inoralsquamouscellcarcinoma,mostofthecon-ductedstudiesfocusedonTILsspecificsub-types,in the majority of cases using immunohistochemistry, but in a minority of studies supported by flow-cytometry [28] and their association with the most important clinical factors -patient's survivals. Stasikowska-Kanickaet alstudiedCD4,CD8,FOXP3, PD-L1 [20] andnaturalkiller(NK)cells [29],Quanet alCD3,CD4,CD8,CD20,CD38,CD40 [28] [22].AlsoBatoolet alstudiedTILslevelatthetumour/hostinterface,in agroupof50patientswithoralsquamouscellcarcinoma,usingathree-tieredscale,asapartoftheir HistologicalRiskAssessment(worstpatternofinvasion, perineural invasion and lymphocytic infiltrate at interface), however, no statistical correlation was observedbetweentheTILslevelandoverallsurvival,localrecurrence-freesurvivalandlymphnoderecurrence-freesurvival [32].Inastudyconductedby Chatzistamou et al in a group of 52 patients with oraltonguesquamouscellcarcinoma,theTILslevel wasevaluatedintumourstromainatwo-tieredscale andaprognosticsignificancewasobservedbetween TILs level and disease free-survival (DFS), post relapse-survival (PRS) and disease related-mortality (DRM) [23].Xuet alinagroupof202patientswith oralsquamouscellcarcinoma,evaluatedtheTILslevelintumouralstroma,usingathree-tieredscale,and theirfindingsconfirmedthestatisticalcorrelationbe-tweentheTILslevelandadisease-freesurvival(DFS) and disease-specific survival (DSS) [24]. Furthermore, the TILs levels showed statistical correlation with DFS and DSS in univariate Cox-proportional hazard models, which is compatible to our study, where TILs levels correlated with OS and LRFS in univariateCox-proportionalhazardmodels.Inmul-tivariateCox-proportionalhazardmodelsTILslevels showedstatisticalcorrelationwithDFSandDSS(Xu et al) -in our study similar correlation was noted (OSandLRFS).Whatisstriking,thatinbothstudies in multivariate Cox-proportional hazard models the [22].…”
Section: Discussionmentioning
confidence: 99%